2022
DOI: 10.3390/molecules27238174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wet and Dry Micronization on the GC-MS Identification of the Phenolic Compounds and Antioxidant Properties of Freeze-Dried Spinach Leaves and Stems

Abstract: Micronization is an emerging technology used in food production, in which the size of particles is reduced to microns in the processing of plant raw materials and by-products, thus making it an interesting research topic. Spinach stems are by-products of spinach leaf processing, but there is little information regarding their processing and possible reuse. In this study, wet and dry ball mill micronization, in combination with freeze drying, was used to process spinach stems and leaves to obtain functional pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For the longest time (20 MRP), the share of red color a* was highest in the micronized samples, and the share of yellow color b* was highest in the micronized samples (20 MRP). Previous research [ 28 ] has shown that the micronization method affects the color of spinach stems and leaves. In comparison to the control sample and dry micronization, wet micronization produced a darker color.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the longest time (20 MRP), the share of red color a* was highest in the micronized samples, and the share of yellow color b* was highest in the micronized samples (20 MRP). Previous research [ 28 ] has shown that the micronization method affects the color of spinach stems and leaves. In comparison to the control sample and dry micronization, wet micronization produced a darker color.…”
Section: Resultsmentioning
confidence: 99%
“…The content of the other phenolic compounds was not significantly different for all samples tested. In our previous studies [ 28 ] on wet and dry micronization of spinach leaves and stems, it was observed that both dry and wet micronization affected the contents of o-coumaric acid and gallic acid. In addition, dry micronization of spinach leaves increased the content of 3-hydroxyphenylacetic acid, 4-hydroxyphenylacetic acid, and p-coumaric acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several micronization methods, including fine grinding in a ball mill. The efficacy of a ball mill in lowering the particle sizes of various plant materials has been demonstrated [ 11 , 12 ]. A previous study on grape pomace powders demonstrated that grinding these materials boosted the powders’ solubility while decreasing their ability to retain water and bind oil and cations.…”
Section: Introductionmentioning
confidence: 99%